Analisis Profitabilitas Pelaku Usaha Gula Semut di Desa Serayu Larangan - Budiningsih, Sulistyani; Watemin, Watemin; Rahayu, Tri Septin Muji; Biky, Muh Amir (Proceedings Series on Physical & Formal Sciences, 2024)
Research objectives a) Identify the internal and external factors of ant sugar business actors in Serayu Larangan Village, Mrebet District, b) Find out the level of production, production costs, profits and profitability of ant sugar business actors in Serayu Larangan Village, Mrebet District. The research method used was a survey with location determination carried out purposively in Serayu Larangan Village, Mrebet District with a total of 3,831 productive coconut trees managed by 169 craftsmen with an average production reaching 115,050 kg. The sample was determined purposively as many as 20 ant sugar business actors who were considered to represent those who had been working in this profession for more than 3 years and also as their main livelihood. The type of data collected is primary and secondary data through interview, observation and documentation techniques. Qualitative and quantitative data processing techniques. Profitability is the ratio between profit/profit from sales of ant sugar. The results of the research show the identification of internal and external factors in the ant sugar business, including availability of land, availability of raw materials, skills of the perpetrator, availability of labor in the family and sources of capital, market demand, prices of ant sugar products tend to be high, technological developments, and the presence of competitors. from outside villages, and collaboration with outside. Ant sugar business actors in Serayu Larangan Village, Mrebet District have an average total cost structure of IDR 94,952.37,- with an average of IDR 159,732.50,-. The gain or profit was IDR 64,780.13, - with a profitability value of the ant sugar business actor of 68.22%, meaning that every time IDR 1.00 of production input is used, it will produce a profit of IDR 68.22.